0887 Diaphragm Pacer Malfunctions Requiring Surgical Repair in CCHS Patients. (27th May 2020) - Kiang, J B; Kun, S S; Shin, C; McComb, G J; Keens, T G; Perez, I A
Abstract: Introduction: Congenital Central Hypoventilation Syndrome (CCHS) is a genetic disorder that results in the loss of autonomic ventilatory control, and patients require ventilatory support during sleep or both sleep and wakefulness. One method of ventilatory support is diaphragm pacing (DP), where electrodes surgically placed on the phrenic nerve are connected to subcutaneously implanted receivers that communicate with external antennas and transmitter. There are limited data on the frequency of DP malfunctions that require surgical revision. Methods: We reviewed the records of 24 CCHS patients ventilated by DP followed at CHLA from 1990-2019. Records were examined for demographics, PHOX2B mutation, pacing duration/day, date and type of malfunctions, age and time since implantation at malfunction occurrence, and repair success rate. Results: All 24 patients had thoracoscopic electrode placement. 17/24 (71%) of patients used DP while asleep; 3/24 (13%) during wakefulness only. 4/24 (17%) were not currently using their pacers. 10/24 (42%) patients required at least one surgical intervention (Age at implantation 9 ± 4.6 (SD) years; age at malfunction 12.5 ± 7.4 years). The average time from pacer implantation to malfunction was 3.8 ± 3.5 years. Malfunctions included defective receivers (6), insulation leaks (1), defective electrodes (4), and hardware infection (1). Of 12 unique component repairs, 6/12 (50%) involved changing receivers, 1/12 (8%) involved repairing an insulation leak, 4/12 (33%) involved replacing the electrodes and receivers, and 1/12 (8%) involved hardware extraction. Of the 12 malfunctions, 10 (83%) had successful surgical revision. 2/12 (17%) repairs were not attempted. While awaiting surgical revision, patients were successfully ventilated by unilateral DP. Conclusion: Nearly half of CCHS patients on DP experienced malfunctions within 11 years of implantation. The most common DP repair was receiver replacement. Patients who are waiting for repair often successfully ventilate while pacing unilaterally. Support: None